2019
DOI: 10.1007/s10826-019-01378-9
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Psychosocial Correlates of Unintentional Injuries Among Grade-School Children: A Comparison of Urban and Migrant Students in China

Abstract: Objective To assess the prevalence and characteristics of unintentional injuries among 5 to 9 grades students for both urban and migrant children groups, and probe the major socio-demographic and psychosocial risk factors. Methods A cross-sectional survey was conducted from May to June in 2013 with 2266 urban and 1770 migrant children among 5 to 9 grades from 13 schools in Yinzhou, Southeast China. Unintentional injuries and psychosocial factors were measured via self-administered questionnaires. Descriptive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 57 publications
5
13
3
Order By: Relevance
“…With regards to the pattern of injuries, cut/stab wounds and broken/dislocated bones dominated. The findings corroborate with previous studies in four Asian countries [ 21 ] and Gao et al [ 9 ] in China, where sprain/fracture was also found to be dominant among adolescents. Furthermore, fall and motor-vehicle accident were the most common causes of injuries among these populations.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…With regards to the pattern of injuries, cut/stab wounds and broken/dislocated bones dominated. The findings corroborate with previous studies in four Asian countries [ 21 ] and Gao et al [ 9 ] in China, where sprain/fracture was also found to be dominant among adolescents. Furthermore, fall and motor-vehicle accident were the most common causes of injuries among these populations.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, amphetamine use was independently associated with one or multiple injuries. These findings corroborate [ 9 , 24 ]. A holistic public health strategy is an effective way to tackle substance usage in a school setting which should be enhanced.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations